Respuesta :

Answer:

See Below.

Step-by-step explanation:

Problem #2

We want to find the general expression for the differential equation:

[tex]\displaystyle \frac{dy}{dx} = \frac{9x-2}{3\sqrt{x}}[/tex]

Separation of variables:
[tex]\displaystyle dy = \frac{9x-2}{3\sqrt{x}} \, dx[/tex]

Take the indefinite integral of both sides and integrate:
[tex]\displaystyle \begin{aligned} \int 1 \, dy & = \int \frac{9x-2}{3\sqrt{x}} \, dx \\ \\ y & = \int \frac{9x}{3\sqrt{x}} - \frac{2}{3\sqrt{x}}\,dx \\ \\ & = \int 3 x\cdot x^{-1/2} \, dx +\int -\frac{2}{3}x^{-1/2}\, dx \\ \\ & = 3\int x^{1/2} \, dx -\frac{2}{3}\int x^{-1/2} \, dx \\ \\ & = 3\left(\frac{2}{3}x^{3/2}\right)-\frac{2}{3}\left(2x^{1/2}\right) \\ \\ & = 2x^{3/2} -\frac{4}{3}\sqrt{x} + C\end{aligned}[/tex]

Hence, the general expression is:
[tex]\displaystyle y = 2x^{3/2} -\frac{4}{3}\sqrt{x} + C[/tex]

Problem #3

We want to evaluate the integral:

[tex]\displaystyle \int \left( 5-x^2 + \frac{18}{x^4}\right) \, dx[/tex]

Apply the power rule for integrals:
[tex]\displaystyle \begin{aligned} \int \left(5-x^2+\frac{18}{x^4}\right)\, dx & = \int \left(5x^0-x^2+18x^{-4}\right)\, dx \\ \\ & = 5x-\frac{1}{3}x^3+18\left(-\frac{1}{3}x^{-3}\right) + C \\ \\ & = 5x-\frac{1}{3}x^3 -\frac{18}{3}x^{-3} + C \\ \\ & = 5x-\frac{1}{3}x^3-\frac{6}{x^3} + C\end{aligned}[/tex]

In conclusion:
[tex]\displaystyle \begin{aligned} \int \left(5-x^2+\frac{18}{x^4}\right)\, dx & = 5x-\frac{1}{3}x^3-\frac{6}{x^3} + C\end{aligned}[/tex]

We need to solve two questions first from differential equations and the second one from Integral Calculus, but before starting let's recall the formulae and concepts which will help us a lot in doing the questions:

  • [tex]{\boxed{\displaystyle \bf \int x^{n}\:dx=\dfrac{x^{n+1}}{n+1}+C\:\: , \:\: n\neq -1}}[/tex]

  • [tex]{\boxed{\displaystyle \bf \int \{f(x)\pm g(x)\pm h(x)\pm \cdots\}dx=\int f(x)\: dx\pm \int g(x)\:dx\pm \int h(x)\:dx\pm \cdots}}[/tex]

  • [tex]{\boxed{\displaystyle \bf \int kf(x)\:dx=k\int f(x)\:dx}}[/tex]

  • [tex]{\boxed{\displaystyle \bf \int dx=x+C}}[/tex]

Where , C is the Arbitrary Constant and k being any constant

Question 1 :-

Consider the differential equation :-

[tex]{:\implies \quad \sf \dfrac{dy}{dx}=\dfrac{9x-2}{3\sqrt{x}}}[/tex]

[tex]{:\implies \quad \sf dy=\dfrac{9x-2}{3\sqrt{x}}dx}[/tex]

Seperate the denominators of the fraction in RHS

[tex]{:\implies \quad \sf dy=\bigg(\dfrac{9x}{3\sqrt{x}}-\dfrac{2}{3\sqrt{x}}\bigg)dx}[/tex]

[tex]{:\implies \quad \sf dy=\bigg(3\sqrt{x}-\dfrac{2(x)^{\footnotesize -\dfrac12}}{3}\bigg)dx}[/tex]

Integrating both sides ;

[tex]{:\implies \quad \displaystyle \sf \int dy=\int \bigg(3\sqrt{x}-\dfrac{2(x)^{\footnotesize -\dfrac12}}{3}\bigg)dx}[/tex]

[tex]{:\implies \quad \displaystyle \sf y=\int 3(x)^{\footnotesize \dfrac12}\:dx-\int \dfrac{2(x)^{\footnotesize -\dfrac12}}{3}\:dx}[/tex]

[tex]{:\implies \quad \displaystyle \sf y=3\int (x)^{\footnotesize \dfrac12}\:dx-\dfrac23 \int (x)^{\footnotesize -\dfrac12}\:dx}[/tex]

[tex]{:\implies \quad \displaystyle \sf y=3\times\dfrac{(x)^{\footnotesize \dfrac32}}{\dfrac32}-\dfrac{2}{3}\times \dfrac{(x)^{\footnotesize \dfrac12}}{\dfrac12}+C}[/tex]

[tex]{:\implies \quad \bf \therefore \quad \underline{\underline{y=2x\sqrt{x}-\dfrac{4}{3}\sqrt{x}+C}}}[/tex]

Question 2 :-

Refer to the attachment for this answer

Ver imagen Аноним
ACCESS MORE